Etične dileme v delovni terapiji - Pihlar, Zdenka (Rehabilitacija (Ljubljana), 2017)
The paper presents ethical dilemmas in occupational therapy. A literature review finds only a small number of articles that are the result of research on this topic. The articles mainly relate to the philosophy of the new paradigm of the profession and less to the dilemmas of therapists in clinical practice, who must daily take ethical decisions. In Slovenia, the topic of ethical dilemmas in occupational therapy has yet to receive attention. Ethical dilemmas are presented based on the work of the few foreign authors, and based on the author's focused interviews with occupational therapists who have got more than 15 years of experience, as well as her own experience in clinical practice.
Keywords: client-centred practice; delovna terapija; environment; ethical issues; Ethics; etične dileme; na posameznika usmerjen pristop; natural environment; occupational therapy; okolje; Rehabilitation